Remembering Pinochet's Chile : on the eve of London, 1998 - Stern, Steve J., 1951- (Stern, Steve J., 1951- Memory box of Pinochet's Chile ;, 2004)
"In 1998, General Augusto Pinochet was arrested in London on charges of crimes against humanity. All over the world, but especially in Chile, the shocking arrest thrust the former dictator and the atrocities of his regime back into the public eye. During the two years just before the arrest, the renowned historian Steve J. Stern had been in Chile collecting oral histories of life under Pinochet as part of an investigation into the form and meaning of memories of state-sponsored atrocities. In this work, Stern shares the recollections of individual Chileans and draws on their stories to provide a framework for understanding memory struggles in history. At once analytical, poignant, and personal, Remembering Pinochet's Chile offers a human portrait of Chile's memory drama on the eve of the London arrest."--Jacket.